2022
DOI: 10.1101/2022.10.13.512090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological Condition Dependent Changes in Ciliary GPCR Localization in the Brain

Abstract: Primary cilia are small immotile cellular appendages which mediate diverse types of singling and are found on most mammalian cell types including throughout the central nervous system. Cilia are known to localize certain G protein-coupled receptors (GPCRs) and are critical for mediating the signaling of these receptors. Several of these neuronal GPCRs have recognized roles in feeding behavior and energy homeostasis. Heterologous cell line and model systems like C. elegans and Chlamydomonas have implicated both… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Primary cilium elongation could potentially alter the density of signalling molecules present in the primary cilium, thereby affecting downstream signalling (21). Interestingly, it has been suggested that not only the regulation of primary cilium formation but also the modulation of cilium length, formation rate, and receptor localization changes under different physiological conditions in the brain (39).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilium elongation could potentially alter the density of signalling molecules present in the primary cilium, thereby affecting downstream signalling (21). Interestingly, it has been suggested that not only the regulation of primary cilium formation but also the modulation of cilium length, formation rate, and receptor localization changes under different physiological conditions in the brain (39).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the MCH/MCHR1 signaling pathway has a well-defined role in energy homeostasis [for a review see ( Al-Massadi et al, 2021 )]. MCHR1 localizes to cilia in many areas of the mouse and rat brain, including the olfactory bulb, hippocampus, amygdala, hypothalamus, and spinal cord ( Niño-Rivero et al, 2019 ; Diniz et al, 2020 ; Brewer et al, 2022 ). Using optogenetics, and chemogenetics, activation and inhibition of the MCH pathway causes cilia shortening and lengthening, respectively, in the brain as measured with ADCY3s staining ( Alhassen et al, 2022 ).…”
Section: Genetic Mouse Models Of Cilia Associated Obesitymentioning
confidence: 99%